Intentions to select an information technology career : a study of South African women - Parsotam, Poonam (My University, 2011)
In South Africa, the importance of computing and information technology (IT) is increasing. Yet, there is an under representation of women IT employees, this may be due to the low percentage of women obtaining IT degrees. South African women are already seriously underrepresented in the IT field and represent an untapped resource. Therefore attention needs to be directed to factors which effect women’s intentions to pursue IT careers. This study drew on two theoretical perspectives, namely the Theory of Planned Behavior, and Social Cognitive Theory to derive a model of how two important factors, computer selfefficacy, and computer anxiety influence women’s feelings about the impact of computers on their daily lives and society, as well as their understanding of computers (i.e. computer attitude). The model further depicted the direct effect of computer attitude. Women’s computer attitudes were also expected to improve once they have received computer training. Although the main focus of the study was towards women’s computer attitude and intention to select an IT career, the study also compared the extent to which gender influences computer self-efficacy, computer anxiety, computer attitude and intention to select an IT career, as well as the relationships that exist between these variables. Hypotheses were thus derived from the model, and uses prior research to argue the validity of the hypotheses. Quantitative data was collected from a sample of 263 first year students from a leading South African University. Statistical analyses of the data revealed that female students intention to select an IT career consisted of two factors namely, IT career interest and perceived tangible rewards. Pearson correlation and multiple regressions were used to test hypotheses. Results revealed that factors such as computer training, computer self-efficacy, computer anxiety, and positive computer attitude influenced IT career interest and perceived tangible rewards. Amongst female students, computer training, computer self-efficacy and perceived tangible rewards impacted IT career interest. This means that if females received computer training, they were more confident towards computers and aware of IT careers prospects, and thus they would be more likely to select an IT career. The study results also detected gender differences which indicated that females are more computer anxious than males, while males are more computer confident and like computers more than females. In addition females are also less likely to select IT careers than males. These results provide important guidance to educational institutes, the IT industry, IT managers, human resource professionals, and other individuals’ interested in career development issues and the gender gap in South African IT.
Keywords: Information technology; Women; Careers